The Effect of Mosquito Biting Rate on the Malaria Transmission Model using Bifurcation Analysis / Zati Iwani Abdul Manaf...[et al.] - Abdul Manaf, Zati Iwani; Rosli, Nur Adiba Lyana; Mahmood, Nurul Aini; Yamin, Noor Alia (2022)
This paper analyses a simple malaria transmission model to investigate the effect of parameter changes in mosquitoes per capita biting rate on human population, β , by using the bifurcation analysis. For further investigation, we first formulated the malaria transmission model into a non-dimensionalized equation. Next, we employed the stability analysis of disease-free equilibrium and endemic equilibrium point of malaria transmission. Using the same non-dimensionalized equation, the one-parameter bifurcation analysis was conducted. A few graphs of the bifurcation diagram, phase plane and time series plot are displayed with the help of mathematical software such as XPPAUT, Maple, and Matlab. Findings reveal that a transcritical bifurcation occurred due to changes in the stability of the system’s equilibrium. When the parameter value of β increases, the infected human and infected mosquito population decreases. This finding demonstrates that changes in mosquito biting rates could have an effect on both infected humans and mosquito population.